PENGARUH PENDAPATAN DAERAH DAN KINERJA KEUANGAN TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT PADA KABUPATEN/KOTA PROVINSI LAMPUNG - Rita Irviani; Citrawati Jatiningrum; Kasmi Kasmi (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2017)
Regional income is one of the important factors in the implementation of government wheels and become one of the important benchmarks in the implementation of regional autonomy. This study aims to test empirically the relationship between regional revenue and financial performance on Economic Growth and Economic Welfare in the Regency/City Lampung Province. The data used are data of regencies/cities in Lampung Province 2014-2016. By using Panel method with fixed method, the result was significant influence between regional income and financial performance to growth economic and welfare society. Empirical evidence indicates that although all regional income variables are influential, the regional restitution has no significant effect on the Welfare of the Community in Lampung Province.